Perspectives in Frontier Culture: New Spain and Homeric Greece - Pi-Sunyer, Oriol (Anthropologica, 1964)
This article intends to examine to what extent the living conditions of a frontier culture lend themselves to the emergence of a new type of culture and personality clearly recognizable. Two historical-cultural situations are analyzed here: New Spain (Mexico), in the years following the Spanish war, and Homeric Greece, a sub-type of Mycean culture. The Ethics of a frontier culture can be seen, in large part, as a functional adjustment to certain situations or factors encountered in all the thousand frontiers. Thus frontier ethics is largely independent of historical-cultural antecedents. Consequently, the adjustments thus made by the intruding groups include a certain discontinuity with the mother culture. Once established,